Effectiveness of prenatal intensive counselling on knowledge, attitude and acceptance of post placental intrauterine contraceptive device among mothers - Shanthini, M; Dash, Manjubala; Chitra, A Felicia; Jayanthi, S; Sujatha, P (Clinical Journal of Obstetrics and Gynecology, 2020)
Introduction: Contraception is a method or device used to prevent pregnancy. In the first year of postpartum period around 65% of women are having unmet need of family planning. Post Placental Intrauterine Contraceptive Device is not only advantageous to the women and couples; even the service providers benefit from PPIUCD. PPIUCD insertion on the same delivery table saves time and separate clinical procedure is not required. Methodology: The Quantitiative Pre-Experimental One Group Pre and Post Test research design was used. 70 Antenatal mothers were selected by using Purposive Sampling Technique who fulfilled the inclusion criteria and who were available during the period of data collection at selected hospital, Puducherrry. Data was collected by using Structured Interview Schedule. Result: The Pre test mean score of Knowledge was 9.98 ± 2.38 and Post Test mean score of Knowledge was 14.91 ± 1.15. The calculated paired‘t’ value was (-20.82) found to be statistically significant at p < 0.001 level. The Pretest mean score of Attitude was 34.67 ± 5.67 and Post test mean score of Attitude was 44.27 ± 4.70. The calculated paired‘t’ value was (-17.25) found to be statistically significant at p < 0.001 level. The Pretest mean score of Acceptance was 0.11 ± 0.320 and Post Test mean score of Acceptance was 0.29 ± 0.455. The paired‘t’ value of t = -3.778 found to be statistically significant at p < 0.001 level. The Demographic and Obstetrical Variables like age at marriage, previous childbirth and decision maker of family about family planning have shown significant association with Post Test level of Knowledge, Attitude and Acceptance of PPIUCD at p < 0.05 and p < 0.001. Conclusion: The researcher concluded that Prenatal Intensive Counselling increases the mother’s Knowledge, Attitude and Acceptance of PPIUCD. So Prenatal Intensive Counselling on PPIUCD can be given to Antenatal Mothers during their antenatal visits to meet the unmet needs of family planning.